Project-Based Learning in Indonesian EFL Classrooms: from Theory to Practice - Yustinus Calvin Gai Mali (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT Project based learning (PBL) refers to an approach to instruction that teaches curriculum concepts through a project espousing principles of learner-centered teaching, learner autonomy, collaborative learning, and learning through tasks. This paper justifies the implementation of PBL to design two main projects and their activities in Creative Writing and Second Language Acquisition classes at English Language Education Program of Dunia University Indonesia (ED-DU). Moreover, the paper details pedagogical practices and learning resources deployed in both classes. The discussions would seem to indicate that the use of PBL grounded in the projects shows a high level of students’ participation in learning, and teachers’ innovative teaching practices. Finally, the paper hopes to provide EFL teachers who have similar teaching practices with practical ideas they can develop to help students achieve particular learning objectives in their classrooms and continue the positive trends of implementing PBL in teaching and learning. ABSTRAK Pembelajaran berbasis proyek (PBL) merupakan suatu pendekatan instruksi yang mengajarkan suatu konsep kurikulum yang didukung prinsip pengajaran yang terpusat pada siswa, otonomi siswa, pembelajaran kolaboratif, dan pembelajaran melalui tugas. Kajian ini memberikan alasan tentang implementasi PBL untuk merancang dua proyek utama dan aktifitasnya di kelas Creative Writing dan Second Language Acquisition pada program studi Pendidikan Bahasa Inggris, Universitas Dunia Indonesia. Selain itu, kajian ini memaparkan secara rinci praktik pedagogi dan sumber pembelajaran yang digunakan di kedua kelas tersebut. Pembahasan dalam kajian ini nampak mengindikasikan bahwa penggunaan PBL dalam kedua proyek tersebut menunjukan tingkat partisipasi siswa yang tinggi dan praktek pengajaran guru yang inovatif. Akhirnya, kajian ini berharap untuk memberikan guru Bahasa Inggris sebagai Bahasa Asing yang mempunyai praktik pengajaran serupa dengan ide praktis yang mereka bisa modifikasi dan kembangkan untuk membantu siswa mencapai tujuan pembelajaran tertentu dalam kelas mereka dan melanjutkan kecenderungan positif pada implementasi PBL dalam pengajaran dan pembelajaran. How to Cite: Mali, Y.,C., G. (2016). Project-Based Learning in Indonesian EFL Classrooms: from Theory to Practice. IJEE (Indonesian Journal of English Education), 3(1), 89-105. doi:10.15408/ijee.v3i1.2651 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.2651